2013
DOI: 10.5539/gjhs.v5n4p189
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Role of Personal, Social and Physical Environment Factors on Employed Women's Physical Activity: A Structural Equation Analysis

Abstract: Background and Objectives:PA is a multi-factorial behavior that is affected by interpersonal, intra personal, environmental and social factors. In this study we applied explanatory model to determine the total, indirect and direct impact of physical environment, personal factors and social support on PA among employed women.Methods:This study was a correlational cross-sectional study which was conducted to model total, indirect and direct impact of environmental, psychological and social factors on PA. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…Social environment questionnaire developed by Sallis and colleagues was applied in order to measure the perceived social support related to the physical activity [30] in which 5 items measure the support provided by friends and coworkers during the past 3 months using a 5-point Likert scale (never to always). To assess the physical environment, Mojahed and colleagues' 8-item questionnaire in 2010 having subscales of availability to facilities, and environmental security and beauty was applied using a 5-point Likert scale [3]. The International Physical Activity Questionnaire (IPAQ) includes 27 items in 4 subscales to measure the physical activity under 4 various situations: at workplace, during leisure times, during commute, and at home.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Social environment questionnaire developed by Sallis and colleagues was applied in order to measure the perceived social support related to the physical activity [30] in which 5 items measure the support provided by friends and coworkers during the past 3 months using a 5-point Likert scale (never to always). To assess the physical environment, Mojahed and colleagues' 8-item questionnaire in 2010 having subscales of availability to facilities, and environmental security and beauty was applied using a 5-point Likert scale [3]. The International Physical Activity Questionnaire (IPAQ) includes 27 items in 4 subscales to measure the physical activity under 4 various situations: at workplace, during leisure times, during commute, and at home.…”
Section: Methodsmentioning
confidence: 99%
“…This can be put into belt or pocket showing the step count and distance walked in mile or kilometer. Researchers have shown that pedometer is a reliable and valid instrument [3,7]. Based on the data obtained by a pedometer, participantc are classified into three categorize based on the number of steps per day: people walking little than 7499 walks a day are considered as immobile ones, while those having 7500-9999 walks a day are moderately active and those who take more than 10000 walks a day are active people [38].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations